Pandangan Hospitalitas Kristen Terhadap Korban Bencana Alam - Julian Eliezer Patendeng (Institut Agama Kristen Negeri Toraja, 2022)
The author through this paper, describes the Christian Hospitality’s view of the victims of natural disasters. It is a behavior that manifests a spirit of family and friendship, so that it is one’s responsibility toward another, as it is an interaction of friendship. Using the quantitative approach of literature of library study with data collection directed to the search of documents and information through books, journals, articles and websites, and apply descriptive methods of interpretative that produce three main points: First, the plurality of societies the experience natural disaster; Second, in the plurality of these disaster victims, Christian hospitality goes to victims of natural disasters; Third, this hospitality can be realized in love for everyone without looking at their identity, “love” can be realized in the service of deacon, prayer and pastoral or psychic mentoring of victims of natural disasters.